Carbon/Binder‐Free NiO@NiO/NF with In Situ Formed Interlayer for High‐Areal‐Capacity Lithium Storage. Issue 14 (14th February 2019) - Li, Yan‐Fei; Shi, Yan‐Hong; Wang, Shu‐Guang; Liu, Jin‐Hua; Lin, Jian; Xia, Yu; Wu, Xing‐Long; Fan, Chao‐Ying; Zhang, Jing‐Ping; Xie, Hai‐Ming; Sun, Hai‐Zhu; Su, Zhong‐Min
Abstract: Achieving high areal capacity is a challenge for current lithium‐ion batteries (LIBs). To address this issue, nickel foam (NF), as a free‐standing skeleton suffers from long‐term poor anchor ability for active materials, resulting in detachment from conductive substrates. In addition, the weighty NF damages the overall energy density of the electrode. Herein, an in situ fabrication of interlayer strategy is proposed to effectively address these issues through constructing layer‐by‐layer a 3D structure composed of an inner conductive framework, medial NiO layer, and outer few‐layer NiO nanoflowers in turn (NiO@NiO/NF). The interlayer derived from partial oxidation of NF not only reinforces the attachment of the active layer on NF but also contributes capacity to the whole electrode, leading to excellent stability and areal capacity. When used as the anode of LIBs, ultrahigh reversible capacity of 1.98 mAh cm −2 is delivered at 1.20 mA cm −2 . The electrode still maintains good integrity and flexibility after 1000 cycles, showing good structure stability. Compared with previous reports, NiO@NiO/NF is one of the most outstanding NiO‐based electrodes. This work proposes a feasible strategy to enhance the capacity and stability of self‐supporting electrodes, and opens a new avenue for high‐areal‐capacity anode of LIBs. Abstract : The five‐layer structure composed of inner conductive framework, medial NiO adhesive, and outer few‐layer NiO nanoflowers in turn is fabricated. The NiO interlayer derived from partial oxidation of NF not only reinforces the attachment of the active layer on NF but also contributes capacity to the whole electrode, leading to excellent stability and areal capacity.